ANALISIS FINANSIEL BEBERAPA PRODUK INDUSTRI KAYU HILIR : Kasus Suatu Perusahaan di Propinsi Kalimantan Selatan (A Financial Analysis on Several, Secondary wood Products : A case of an enterprise in Province South Kalimantan) - Rachman Effendi (Jurnal Penelitian Hasil Hutan, 1993)
Presently, the role of forestry sector in indonesia becomes very important. In 1990/1991,forestry  sector  has contributed the second largest foreign  exchange after oil and gas.  For the last few  years,  a transition has taken place  in the forest  industries, namely from primary industries to secondary   or tertiary industries which is expected to increase added value of forest products.  The objective of this study is to analize.  the profitability of an enterprise producing several secondary products such as moulding, dowet, jointed  board, finger jointed product, and table top.The results showed    that annual production  of moulding, dowel, jointed board, finger jointed   product,  and table top were 26.880 m3,  12,000 m3, 5.760 m3, 5.760 m3, and 2,880 m3. respectively. Production costs per cubic meter of moulding, dowel, jointed  board, finger  jointed  product,   and  table  top  were  Rps 618.053,-,  Rps    612.333,-,  Rps  631.537,-,  Rps  622.967,-  and  Rps 654.417,-, respectively. Payback period  was relatively short (4.04 years),  Net present  value (NPV) showed positive  value, and internal rate of return  (IRR) was higher than  average  bank interest. However,  NPV was sensitive to a decrease  in production,   15  %  decrease  in production would cause NPV to become negative.